2015
DOI: 10.1016/j.landurbplan.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Millipede (Diplopoda) assemblages alter drastically by urbanisation

Abstract: Any queries or remarks that have arisen during the processing of your manuscript are listed below and highlighted by flags in the proof. Click on the 'Q' link to go to the location in the proof. Location inQuery / Remark: click on the Q link to go article Please insert your reply or correction at the corresponding line in the proof Q1Please confirm that given names and surnames have been identified correctly. Q2The decimal commas have been changed to decimal dots for "chi 2 " values. Please check and correct i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
7
19
0
2
Order By: Relevance
“…Most of the recorded species are widespread in Europe [41,42]. Millipedes from urban and other anthropogenic habitats were previously investigated in several European cities [43][44][45][46][47][48][49][50][51][52][53]. Discussing some of these data, Vilisics et al [53] stated that urban areas can be characterized by 14-26 species on average.…”
Section: Diplopoda Fauna Of Budapestmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the recorded species are widespread in Europe [41,42]. Millipedes from urban and other anthropogenic habitats were previously investigated in several European cities [43][44][45][46][47][48][49][50][51][52][53]. Discussing some of these data, Vilisics et al [53] stated that urban areas can be characterized by 14-26 species on average.…”
Section: Diplopoda Fauna Of Budapestmentioning
confidence: 99%
“…Mwabvu [55], studying spirostreptid millipedes, also reported that species richness decreased with increasing urban disturbance. In a rural-urban gradient study (Debrecen, Hungary), Bogyó et al [43] found the highest millipede abundance, species richness, and diversity in the suburban area. Higher functional diversity of millipedes was observed in less urbanized habitats that are rich in decaying wood and leaf litter, as reported by Nagy et al [56] for woodlice.…”
Section: Urban Effects On Taxonomic/functional Diversity and Compositmentioning
confidence: 99%
“…Each hypothesis is supported by published studies, but numerous variations occur, and many authors have opted to 'test' for one or other hypothesis, rather than the full possible range. For millipedes ( Diplopoda ) in Hungary, Bogyo et al ( 2014 ) found considerable support for the intermediate disturbance hypothesis, with numbers of individuals and species richness signifi cantly highest in suburban areas, with (1) the ratio of forest specialist individuals and species decreasing along the rural-urban gradient, and (2) the ratio of synanthropic individuals and species increasing significantly. Average body size was lower in urban areas than elsewhere.…”
Section: Introduction: Values Of Gradient Studiesmentioning
confidence: 92%
“…Size differences correlate with factors such as color, sexes, species, urbanisation and water relations [7][8][9][10][11] . Diplopoda resemble the majority of invertebrates where SSD is reversed [12] .…”
Section: Introductionmentioning
confidence: 99%